4-Chloro-N-(3,4-dimethylphenyl)benzenesulfonamide - Gowda, B. Thimme (International Union of Crystallography, 2010)
In the title compound, C(14)H(14)ClNO(2)S, the angle between the sulfonyl and aniline benzene rings is 65.5 (1)°. The crystal structure features inversion dimers linked by pairs of N—H⋯O hydrogen bonds. The dimethylphenyl ring is disordered over two different orientations approximately related by a 180° rotation about the C—N bond, with occupancies of 0.643 (6) and 0.357 (6).